2001
DOI: 10.1038/nn767
|View full text |Cite
|
Sign up to set email alerts
|

Inferotemporal neurons represent low-dimensional configurations of parameterized shapes

Abstract: articlesThe capacity to categorize stimuli is fundamental to all living organisms 1,2 . Theories of categorization agree upon the importance of the similarity between stimuli to account for many aspects of categorization performance [3][4][5] . However, it is not straightforward to compute the degree of similarity between stimuli that can vary across a high number of dimensions, like complex shapes. Fortunately, the similarities among a set of complex stimuli can often be described in a more compact way [6][7]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
259
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(288 citation statements)
references
References 42 publications
24
259
2
1
Order By: Relevance
“…Some of the most remarkable findings about anterior IT concern the highly selective neuronal tuning for complex visual patterns reported by some authors (Desimone et al, 1984;Logothetis et al, 1995;Op de Beeck et al, 2001;Brincat and Connor, 2004;Freedman et al, 2005;Brincat and Connor, 2006) and the very high tolerance to stimulus transformations reported by others (Gross et al, 1972;Desimone and Gross, 1979;Perrett et al, 1982;Rolls and Baylis, 1986;Tovee et al, 1994;Rolls, 2000). Remarkably however, to our knowledge, no previous study has investigated the possible connection between these properties in IT.…”
Section: Discussionmentioning
confidence: 79%
“…Some of the most remarkable findings about anterior IT concern the highly selective neuronal tuning for complex visual patterns reported by some authors (Desimone et al, 1984;Logothetis et al, 1995;Op de Beeck et al, 2001;Brincat and Connor, 2004;Freedman et al, 2005;Brincat and Connor, 2006) and the very high tolerance to stimulus transformations reported by others (Gross et al, 1972;Desimone and Gross, 1979;Perrett et al, 1982;Rolls and Baylis, 1986;Tovee et al, 1994;Rolls, 2000). Remarkably however, to our knowledge, no previous study has investigated the possible connection between these properties in IT.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, IT neurons also show selectivity for other features, including object shape 50,51 , viewpoint 52 , position 53,54 and size 53 . These results are in accordance with the findings from fMRI adaptation studies in humans.…”
Section: Monkey Studiesmentioning
confidence: 99%
“…4). Furthermore, it has been shown that single cells and columns in the monkey IT cortex are selective for moderately complex features 96,97 ; that neurons in v4 and in the posterior IT cortex are tuned for simple shape characteristics 98,99 ; and that IT neurons exhibit gradual tuning in simple shape spaces 50,51 . Finally, single-cell recordings and fMRI studies have provided evidence of selectivity for object parts and non-accidental properties (for example, symmetry, parallelism and collinearity) in the ventral temporal cortex 49,100 , as predicted by structural description theories of object recognition 101,102 .…”
Section: Basic Properties In the Ventral Visual Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent successful attempts to apply psychometric classification techniques directly to physical parameter space rather than similarity space (Op de Beeck, Wagemans & Vogels, 2001;Peters, Gabbiani & Koch, 2003) the difficulties in relating perceived similarity to physical stimulus properties have been abundant, and historically were part of the motivation for the development of MDS (Shepard, 1987). Specifically, for compound gratings as used in the present study MDS dimensions only partly correlate with the dimensions of the generating Fourier feature space (Kahana & Bennett, 1994), and confusion errors are predicted neither by pixel-wise pattern correlation (Jüttner et al, 1997) nor by image representations based on Laplacian pyramids or 2D…”
Section: Discussionmentioning
confidence: 99%